2012
DOI: 10.1258/la.2012.012028
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary ingestion of nut paste for administration of buprenorphine in rats and mice

Abstract: An adequate analgesic strategy is important to improve the postoperative recovery and welfare of laboratory rats and mice. It is desirable that the method for administering the drug is non-invasive and stress-free. We have previously validated a method for administering buprenorphine in a nut paste for voluntary ingestion. This method has many advantages over parenteral administration. To use the method in a successful way, however, it is important to prepare and administer the mix correctly. The present paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…An analgesic regimen, consisting of 1 mg/kg body weight (BW) buprenorphine (Temgesic; Schering-Plough Europe, Brussels, Belgium) was given in nut paste (Nutella®, Ferrero, Pino Torinese, Italy) for voluntary ingestion prior to surgery and then once daily for two days post-surgery, as described previously [21,22]. To ensure adequate pre-emptive analgesia, the mice were injected with 0.1 mg buprenorphine/ kg BW before being brought out of anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…An analgesic regimen, consisting of 1 mg/kg body weight (BW) buprenorphine (Temgesic; Schering-Plough Europe, Brussels, Belgium) was given in nut paste (Nutella®, Ferrero, Pino Torinese, Italy) for voluntary ingestion prior to surgery and then once daily for two days post-surgery, as described previously [21,22]. To ensure adequate pre-emptive analgesia, the mice were injected with 0.1 mg buprenorphine/ kg BW before being brought out of anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The voluntary consumption of an acute poison is both a novel and realistic model for mass-poisoning scenarios. Much of the literature that uses voluntary consumption falls into one of several types: chronic low-level exposures (e.g., [39]), descriptions and analyses of events that previously occurred (e.g., [40, 41]), masking/delivering medicinal doses (e.g., [42–44]), or delivering a substance that has reinforcing properties on its own, such as ethanol or morphine [4548]. There is a severe lack of information regarding the oral consumption of acute poisons, despite the fact that many chemicals are oral hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Bupenorphine can be administered subcutaneously or orally in rats and mice (Liles and Flecknell, 1992a, Volker et al, 2000, Abelson et al, 2012 and has shown to be effective in treating multiple pain conditions including neuropathic pain (Guarnieri et al, 2012). Preanaesthetic subcutaneous (SC) administration of buprenorphine, during ketamine-medetomidine injectable anaesthesia, was associated with respiratory arrest and mortality in rats (Hedenqvist et al, 2000).…”
Section: Buprenorphine Is the Most Commonly Used Rodent Analgesic Agentmentioning
confidence: 99%